2017
DOI: 10.33546/bnj.72
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato (Ipmoea Batatas L.) Leaf: Its Effect on Prolactin and Production of Breast Milk in Postpartum Mothers

Abstract: Background: Sweet potato leaf is assumed to be one of alternative herbs that can increase breast milk production. However, there was no studies found in the literature that examine the sweet potato leaves to increase the levels of prolactin and milk production.Objective: To examine the effect of sweet potato (Ipomoea batatas L.) leaf on the levels of prolactin and milk production in postpartum mothers.Methods: This was a Quasy experimental study with pretest-posttest design with control group, conducted on Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This is because the content in herbs can stimulate milk production. Herbal plants, such as purple sweet potato leaves, Research conducted by Kusuma, Setiani, Umaroh, Pramono, Widyawati, and Kumorowulan, (2017) at Boyolali Community Health Center using a quasi-pretest-posttest design on 30 postpartum mothers using an enzyme-linked immunosorbent assay (ELISA) to measure prolactin levels, while breast milk production measured based on breastmilk volume and infant weight, the results showed that purple sweet potato leaves can significantly increase prolactin levels and the amount of breast milk. This is because sweet potato leaves contain lipid structure elements and hormones in which active compounds are actively involved in milk production because they performed a lactagogue effect.…”
Section: The Use Of Herbs To Increase Breastmilk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the content in herbs can stimulate milk production. Herbal plants, such as purple sweet potato leaves, Research conducted by Kusuma, Setiani, Umaroh, Pramono, Widyawati, and Kumorowulan, (2017) at Boyolali Community Health Center using a quasi-pretest-posttest design on 30 postpartum mothers using an enzyme-linked immunosorbent assay (ELISA) to measure prolactin levels, while breast milk production measured based on breastmilk volume and infant weight, the results showed that purple sweet potato leaves can significantly increase prolactin levels and the amount of breast milk. This is because sweet potato leaves contain lipid structure elements and hormones in which active compounds are actively involved in milk production because they performed a lactagogue effect.…”
Section: The Use Of Herbs To Increase Breastmilk Productionmentioning
confidence: 99%
“…katuk leaves, turmeric, lempuyangan, tamarind, green bean extract, and dates if consumed regularly, would increase the amount of prolactin and breastmilk(Baequny, 2016;Kusuma, Setiani, Umaroh, Pramono, Widyawati, and Kumorowulan , 2017;Sakka, Salama, and Salama, 2014; Wulandari and Jannah, 2015).…”
mentioning
confidence: 99%